Elastic, optical and structural features of wide range of CdO- Na2B4O7 glasses. (8th June 2018) - Saddeek, Y B; Aly, K A; Shaaban, Kh S; Ali, Atif Mossad; Sayed, M A
Abstract: Wide range of CdO—Na2 B4 O7 glasses have been prepared and characterized via XRD, FTIR and UV spectroscopies along with DTA and ultrasonic techniques. The compositional dependence of the physical parameters such as the density, the molar volume, the optical transmittance, the optical band gap, the ultrasonic velocities and the elastic moduli on CdO content were determined. The profiles of XRD assured the amorphous nature of the explored glasses. The clarification of the borate and cadmium functional groups besides their linkages was extracted from the deconvoluted FTIR spectra. Such a clarification was used in the analysis of the relation of the mechanical, T g and optical parameters versus CdO content. These physical parameters revealed the glass modifier role of CdO.